Influence of the Executive Authority on Legislative Authority Under Constitution of 2005 of Republic of Iraq - Abood Faisal, Najam (Opción, 2019)
The executive Authority in the parliamentary system enjoys having its means tointerfereintheworkoftheparliament,includingits conveninganddissolv- ing, and the right to reject its laws. The most significant means is demanding solving the parliament. It is considered a constitutional action that shall make an unnatural end of the parliament within one elections course. This demand must be based on constitutional reasons. The aim behind the idea of a solution is to achieve a balance between the executive and legislative authorities. It is a right owned by the government in exchange for the ministerial responsibility of the legislature to withdraw confidence from the government .There is no doubt that the right to dissolve the parliament is the most serious right stated, however, the executive authority may deliberately use such right as a means to put pressure on the legislature, making it unable to cope with the government.